Konsumsi Sinergistik Produk Kecantikan (Studi Pembentukan Perilaku Konsumsi Sinergistik Pada Komunitas Perempuan Muslimat di Surabaya Oleh Produsen Kosmetik X) - Ratna Azis Prasetyo; Udji Asiyah (MediaTrend, 2018)
In a social reality, "beauty" is constructed through certain standards to produce a common beauty standard. The capitalists through advertising do not propose beauty as a natural and relative thing but are made in a common standard according to the measures they made for the marketing of their products. Through advertising, capitalists are also targeting Muslim women community who are very large in Indonesia as a market share. They use religious symbols, as seen in beauty product advertisements they feature many hijab-wearing models. This study aims to examine the discourse about the commodified beauty and ultimately provide economic value for products, especially beauty products. The capitalists then diversify the product, either by adding a variety of products or making derivative products. The goal is to form a synergistic consumption of its consumers. They held beauty talk shows in the form of Islamic recitation as an attempt to attract the interest of Muslim women's communities. This study uses a cultural studies approach to explain how the behaviour of synergistic consumption is formed. The results of this study concluded that the synergistic consumption of informants by consuming product variation or consuming derivative products from beauty products is started from beauty vitamin, then continued on body lotion, face cream, and face toner.Keyword: Beauty, Women, Synergistic Consumption, Cultural Studies